ANTERIOR CERVICAL CORPECTOMY WITH ILIAC CREST BONE GRAFT VERSUS TITANIUM MESH CAGE IN DEGENERATIVE CERVICAL SPONDYLOTIC MYELOPATHY: A TERTIARY CARE CENTER EXPERIENCE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Degenerative cervical spondylotic myelopathy (DCSM) is a leading cause of progressive spinal cord dysfunction in adults. Anterior cervical corpectomy with reconstruction is a well-established surgical approach for multilevel ventral compression. Various reconstruction options exist, including autologous iliac crest bone grafts and titanium mesh cages. Objective: To evaluate and compare clinical and radiological outcomes following anterior cervical corpectomy reconstructed using iliac crest bone graft or titanium mesh cage in patients with DCSM. Methods: This prospective observational study included 60 patients with DCSM who underwent anterior cervical corpectomy between August 2021 and December 2025. Single-level corpectomy was performed in 52 patients, while 8 patients underwent two-level procedures. Clinical outcomes were assessed using the modified Japanese Orthopaedic Association (mJOA) score and Nurick grading. Radiological evaluation included fusion status, cervical alignment, graft subsidence, and implant-related complications. The minimum follow-up duration was 3 years. Results: All patients demonstrated significant postoperative neurological improvement. The mean mJOA score improved from 9 preoperatively to 14 at final follow-up. Fusion rates were comparable between both groups. Donor-site complications were observed exclusively in the iliac crest group, whereas cage subsidence occurred more frequently in the titanium mesh group without affecting clinical outcomes. Conclusion: Both reconstruction techniques provide satisfactory clinical and radiological outcomes. Titanium mesh cages offer comparable fusion rates while avoiding donor-site morbidity, making them an effective alternative to autologous bone grafts.